Sign language in Indo-Pakistan : a description of a signed language - Zeshan, Ulrike (John Benjamins Pub. Co., 2000)
To find a suitable framework for the description of a previously undocumented language is all the more challenging in the case of a signed language. In this book, for the first time, an indigenous Asian sign language used in deaf communities in India and Pakistan is described on all linguistically relevant levels. This grammatical sketch aims at providing a concise yet comprehensive picture of the language. It covers a substantial part of Indopakistani Sign Language grammar. Topics discussed range from properties of individual signs to principles of discourse organization. Important aspects of.